The Role of Moral Obligation in Enhancing Social Entrepreneurial Intention: The Mediating Role of the Entrepreneurial Event Model - Kurjono; Sulthan Yusuf Abdullah (Dinamika Pendidikan, 2026)
This study aims to examine the predictors of social entrepreneurial intention, namely empathy and moral obligation, among vocational high school students (SMKN) in Bandung City, with perceived behavioral control as a mediating variable. It is hypothesized that empathy and moral obligation positively influence students’ social entrepreneurial intention. This research employs a quantitative survey method, with data collected through questionnaires. The population consists of accounting-track students from public vocational high schools (SMKN) across Bandung City, with a sample size of 212 respondents. Data were analyzed using regression analysis with SmartPLS version 3. The results indicate that perceived behavioral control fully mediates the effect of empathy on social entrepreneurial intention, while it partially mediates the effect of moral obligation on social entrepreneurial intention. These findings suggest that moral obligation and entrepreneurial self-efficacy are important factors that should be maintained and enhanced to foster social entrepreneurial intention among vocational high school students in Bandung City.